Health Related Quality of Life among People Living with HIV /AIDS in Pakistan - Bizanjo, Mahwash; Salahuddin, Naseem (Infectious Diseases Journal of Pakistan, 2023)
Objective: To assess quality of life in HIV /AIDS patients on Anti-retroviral therapy using WHO QOL- BREF instrument. Study design: Cross sectional study. Place and duration of study: The study was conducted in outpatient department of The Indus Hospital, Karachi from January to July 2016. Methodology: Quality of life (QOL) was evaluated using the WHO QOL BREF instrument (translated Urdu version) using 31 items grouped under 6 domains: namely physical, psychological, level of dependence, social relations, environment and spirituality. The demographics along with CD4 counts, stage of disease and viral loads and duration of Anti-retroviral therapy were recorded. It was a cross sectional study and sample size was 109 patients. Data was entered and analyzed using SPSS version 21.0. The equation suggested by WHO was applied to overall estimation of each domain with scores ranging from 4 to 20. Results: A total of 109 participants completed the questionnaire out of which 76 (69.7%) were males, 28 (25.7%) were females and 3 (1.8%) were transgender. Mean (SD) age of patients was 39.2 (10.9) years. Regarding marital status 77(70.6%) were married, 20(18.3%) were single, 4(3.7%) were divorced and 7(6.4%) were widowed. Majority 94 (86.2%) had revealed their serostatus to their relatives and 8 (7.3%) did not reveal their illness99 (90.8%) were in stage 1 of AIDS, 5 (4.6%) were in stage 2, 1 (0.9%) were in stage 3 and 4respectively. Majority of patients were illiterate comprising 36 (33%), 21(19.3%) had primary/middle education, 18(16.5%) had degree graduation and bove. Regarding marital status 77(70.6%) were married, 20(18.3%) were single, 4(3.7%) were divorced and 7 (6.4%) were widowed. Highest scores were noted in domains of physical health, spiritual, and religious beliefs. (Median scores 15 in both). Psychological domain scored average, social relations and environment were the two domains in which low scores were noted as compared to other domains. Overall the quality of life of the patients was found to be fair to average. (Mean score: 13.7). Conclusion: Our study WHO-QOL BREF instrument Urdu version showed that QOL scores were high in physical health, spirituality/ religious domains, fair scores were obtained in psychological domains whereas social relations, and environmental aspects scored less. Key words: WHO QOL BREF, HIV, and AIDS